The Child Welfare Employees’ Constructions of Contact Visits for Parents and Children in Public Care - Marianne Buen Sommerfeldt; Hilde Anette Aamodt (Social Sciences)
Following a care order, children and parents are entitled to contact with each other in accordance with the conditions established by the Child Welfare Tribunals. How child welfare employees understand what contact visits can be and how they can be structured in line with the best interests of the child is crucial in their decision making. This article explores the different constructions of contact visits, in terms of how employees communicate their understanding of access arrangements. This article draws on recordings of child welfare employees discussing the structuring and extent of contact between parents and children in public care. The analysis explored the material in line with Luhmann’s communication theory and found that the dimensions in which the employees communicated produce the ways in which the contact visits are constructed. The ways in which the contact visits were constructed varied, and the factual dimension, temporal dimension, and social dimension were interdependent in the communication. This article demonstrates the impact of employees’ communication in assessing and constructing contact visits for the access arrangements for the individual child and encourages awareness of the factors that are emphasized. This article highlights the need for discussions grounded in social work perspectives to ensure individualized access arrangements. The article contributes to rethinking understandings of how to construct contact visits, while urging critical reflection on the power of child welfare employees in determining how contact visits should be structured.